KIF21B Expression in Osteosarcoma and Its Regulatory Effect on Osteosarcoma Cell Proliferation and Apoptosis Through the PI3K/AKT Pathway - Ni, Songjia; Li, Jianjun; Qiu, Sujun; Xie, Yingming; Gong, Kaiqin; Duan, Yang (Frontiers in Oncology, 2021)
Osteosarcoma (OS) is the most common malignancy that occurs mainly during childhood and adolescence; however, no clear molecular or biological mechanism has been identified. In this study, we aimed to explore new biomarkers for the early diagnosis, targeted treatment and prognostic determination of osteosarcoma. We first used bioinformatics analysis to show that KIF21B can be used as a biomarker for the diagnosis and prognosis of osteosarcoma. We then examined the expression of KIF21B in human osteosarcoma tissues and cell lines using immunohistochemistry, western blotting and qRT-PCR. It was found that KIF21B expression was significantly upregulated in osteosarcoma tissues and cell lines. After knocking down the expression of KIF21B in the osteosarcoma cell lines 143B and U2-OS, we used cell fluorescence counting, CCK-8 assays, flow cytometry and TUNEL staining to examine the effects of KIF21B on osteosarcoma cell proliferation and apoptosis. The results demonstrated that knocking down KIF21B in 143B and U2-OS cells could increase cell apoptosis, inhibit cell proliferation and reduce tumor formation in nude mice. Subsequently, we used gene chips and bioinformatics to analyze the differential gene expression caused by knocking down KIF21B. The results showed that KIF21B may regulate OS cell proliferation and apoptosis by targeting the PI3K/AKT pathway. We then examined the expression of PI3K/AKT- and apoptosis-related proteins using western blotting. KIF21B knockdown inhibited the PI3K pathway, downregulated Bcl-2 and upregulated Bax. Moreover, the use of PI3K/AKT pathway agonists reversed the regulatory effect of KIF21B on the apoptosis and proliferation of 143B and U2-OS cells. In conclusion, our results indicated that KIF21B plays a key role in osteosarcoma. Low KIF21B expression might indirectly increase the apoptosis and inhibit the proliferation of osteosarcoma cells through the PI3K/AKT pathway.